Clinical characteristics and therapeutic behavior of breast cancer patients using mistletoe therapy consulting a clinic offering integrative oncology: a registry data analysis - Daniel Krüerke; Marianne Schenker; Klazien Matter-Walstra (BMC, 2023)
Abstract Motivation Cancer patients often use complementary and/or alternative medicine, such as mistletoe therapy, alongside conventional cancer therapies. In Switzerland, so far not much is known about treatment patterns of breast cancer patients using integrative oncology. Solid knowledge on complementary care utilization may help to enhance integrative oncology care in Switzerland. Methods In this exploratory, descriptive database study, we investigated the treatment pathways of a cohort of breast cancer patients who received mistletoe therapy and were documented in the cancer registry of an anthroposophic Swiss hospital offering integrative oncology treatments. Results Patients treated with mistletoe in this cohort are in median 10 years younger than Swiss breast cancer patients as a whole. Only 5.8% of these patients were treated with mistletoe alone, while 60.5% of them supplemented chemotherapy and/or hormone therapy and/or surgery and/or radiation with mistletoe therapy. Nearly 80% of patients started conventional therapy followed by additional mistletoe therapy or started mono mistletoe therapy after completion of conventional therapies. The median time from initial diagnosis to hospital admission (inpatient and/or outpatient) was less than one year. Almost ¾ of the patients were treated in an outpatient setting only. Conclusion From our data, it appears that younger breast cancer patients are more likely to use mistletoe therapy simultaneously with or following their conventional medical therapies. The extent to which these patients discuss their mistletoe therapy and eventually other complementary and/or alternative therapies with their primary oncologists is not clear from the data. We therefore recommend that (Swiss) oncologists should openly discuss the desire for integrative oncology therapies, especially with their younger breast cancer patients, in order to find the best holistic care pattern for these patients.